Juridical Implication of Restorative Justice On Prosecutorial Authority In Penal Mediation - I Gde Putu Prema Dhananjaya; Milda Istiqomah; Abdul Madjid (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The development of criminal law in Indonesia shows a paradigm shift from a retributive approach to a restorative approach that emphasizes the restoration of victims' losses, the responsibility of perpetrators, and the restoration of social relations. This shift is marked by the presence of a Restorative Justice mechanism in the National Criminal Procedure Code (KUHAP), which can be implemented from the investigation, inquiry, prosecution, to trial. On the other hand, the Prosecutor's Office Law has previously authorized Prosecutors to conduct Penal Mediation as a form of out-of-court criminal case resolution. This condition raises legal issues in the form of potential overlapping authority, dualism in case resolution mechanisms, and unclear relationships between Restorative Justice and Penal Mediation in the national criminal justice system. This research uses a normative legal method with a statutory, conceptual, and systematic approach. Primary legal materials consist of laws and regulations related to the National Criminal Procedure Code, the Prosecutor's Office Law, and other relevant provisions, while secondary legal materials are obtained from literature, journals, and legal doctrine. The research findings indicate that the presence of Restorative Justice mechanisms strengthens the humanist orientation in law enforcement, but simultaneously demands harmonization of norms so that the Prosecutor's authority in Penal Mediation maintains legal certainty. Penal Mediation is essentially a special instrument within the Restorative Justice framework that can be optimized at the prosecution stage. Going forward, regulatory reform is needed that clarifies the limits of authority, implementation procedures, case criteria, and legal consequences of restorative resolution to create an effective, simple, and just criminal justice system.